Impact of Influencing Strategy Across Product Categories in Family Decision Making - Menon, Swapna; Gahan, Padmabati; Mahapatra, Siba Sankar (Indian Journal of Marketing, 2019)
Understanding decision-making within families has gained a lot of interest in behavioral studies. The involvement of various participants in family decision-making environment has been a focus for researchers to know their degree of influence in family decision making. Children are emerging as an important entity in the modern family structure capable of taking buying decisions or influencing it. The role children play in family as deciders and the strategies they adopt to persuade family members is vital to focus and determine the marketing strategies companies could adopt to influence them. In the context of marketing, children socialize to become consumers and their evolution as customers can be captured very well by analyzing the interplay of socialization process and the respective agents like parents, friends, etc. that influence their attitudes and market related behavior. This paper focused on Indian children and their purchase behavior with respect to the influencing strategies they adopted to convince parents in family shopping behaviour. The paper found that children used different influencing strategies across different product categories.